Analisis Kualitas Layanan Daerah Air Minum terhadap Kepuasan Pelanggan : Studi pada PDAM Bersujud Kabupaten Tanah Bumbu Kalimantan Selatan - Raudatul Jannah; Anwar Ramli; Muhammad Ilham Wardhana Haeruddin; Siti Hasbiah; Muhammad Ichwan Musa (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
This research aims to determine the effect of service quality on customer satisfaction at the Regional Water Utility (PDAM Bersujud) in Tanah Bumbu Regency. The independent variable in this study is service quality, while the dependent variable is customer satisfaction. This is a quantitative study employing a descriptive approach. The sample consists of 100 individuals, all active customers of the Regional Water Utility Bersujud in Tanah Bumbu Regency up until 2023. Data collection was carried out using a questionnaire survey method. The data analysis technique utilized statistical tests, including Regression and t-tests, with the help of Statistical Product and Service Solution (SPSS) software. The results of this study indicate that service quality (X) has a positive and significant effect on customer satisfaction (Y) at the Regional Water Utility (PDAM) Bersujud in Tanah Bumbu Regency.